2006
DOI: 10.1111/j.1365-2249.2006.03076.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating IgA from acute stage of childhood Henoch-Schönlein purpura can enhance endothelial interleukin (IL)-8 production through MEK/ERK signalling pathway

Abstract: SummaryRecently, sera from children with active Henoch-Schönlein purpura (HSP) have been found to enhance interleukin (IL)-8 production by human umbilical venous endothelial cells (HUVEC). To further determine the possible factor with the ability to enhance endothelial IL-8 production in sera from acute stage of HSP, 10 children with HSP at the acute stage and 10 healthy controls were enrolled. IgA antiendothelial cell antibodies (AECA) were detected by cell-based ELISA. Active sera with or without pretreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 31 publications
2
58
0
1
Order By: Relevance
“…Furthermore, the presence of the PspC-or FHspecific antiserum reduced adherence to HUVEC, suggesting that the PspC-FH interaction was responsible for enhanced pneumococcal adherence. Additional studies are required to fully investigate the mechanisms by which FH and sIgA mediate adherence to this cell type; however, increased pneumococcal adherence caused by the presence of sIgA may be attributed to direct binding of IgA to endothelial cells (46). Furthermore, we demonstrated that FH binding is more important in pneumococcal adherence to lung epithelial cells (SK-MES-1) than sIgA binding.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the presence of the PspC-or FHspecific antiserum reduced adherence to HUVEC, suggesting that the PspC-FH interaction was responsible for enhanced pneumococcal adherence. Additional studies are required to fully investigate the mechanisms by which FH and sIgA mediate adherence to this cell type; however, increased pneumococcal adherence caused by the presence of sIgA may be attributed to direct binding of IgA to endothelial cells (46). Furthermore, we demonstrated that FH binding is more important in pneumococcal adherence to lung epithelial cells (SK-MES-1) than sIgA binding.…”
Section: Discussionmentioning
confidence: 81%
“…Although the presence of IgA ANCA is still being debated (Ozaltin et al 2004), other autoantibodies such as IgA anti-cardiolipin antibodies or IgA rheumatoid factors have been described (Saulsbury 1992;Yang et al 2000). Recent studies by Yang et al reported that circulating IgAs in HSP are directed against endothelial cells and that these antibodies are able to activate endothelial cells triggering their IL-8 production (Yang et al 2002;Yang et al 2006). Hence, the implication of the AECA in the PNN infiltrationanother characteristic feature of the vascular lesion in HSP-has been raised.…”
Section: Henoch-schö Nlein Purpuramentioning
confidence: 93%
“…In ANCA-mediated vasculitis, AECA may thus play an important role by facilitating the neutrophil adherence to endothelium via the upregulation of adhesion molecules on endothelial cells (Del Papa et al 1996). In Henoch-Schönlein purpura (HSP), IgA AECA may enhance the induction of interleukin (IL)-8 production, a neutrophil chemoattractant cytokine (Yang et al 2006), and could thus be involved in the neutrophil recruitment. Finally, the circulating AECA against aortic endothelial cells described in TA may be involved in the disease pathogenesis, not only through the activation of endothelial cells, but also via the induction of apoptosis (Chauhan et al 2006).…”
Section: Anti-endothelial Cell Antibodiesmentioning
confidence: 99%
“…Sera and IgA from patients with HSP induce the secretion of IL-8 from endothelial cells invitro [160,161].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%